Thermal stability of Al-Si12at.% nano-alloys confined between AlN layers in a nanomultilayer configuration. (15th March 2017) - Lipecka, Joanna; Janczak-Rusch, Jolanta; Lewandowska, Malgorzata; Andrzejczuk, Mariusz; Richter, Gunther; Jeurgens, Lars P.H.
Abstract: Nanomultilayers (NMLs) are envisaged for joining miniaturized and heat-sensitive components at ever-reduced temperatures. Investigation of the thermal stability of bulk-eutectic Al-Si12at.% nanolayers, confined between AlN barriers in a NML configuration, evidences the onset of phase separation of the supersaturated Al-Si solid solution into domains of pure Al and pure Si at around 200 °C. The phase-separated, but still nano-confined Al-Si nanolayers develop large in-plane compressive stresses upon further heating, which invoke extensive mass transport of both Si (by solid-state diffusion at T  > 200 °C) and liquid Al (by heterogeneous contact melting at 300 <  T  < 400 °C) to the NML surface. Graphical abstract: The intrinsic thermal instability of nano-confined alloys may invoke a significant melting point depression, which may be exploited for joining miniaturized and heat-sensitive components at ever-lower temperatures.